Vietnam - poor communes livelihoods and infrastructure program project = (The World Bank in VietNam (WB), 2004)
The proposed operation would reduce poverty and foster secure and sustainable livelihoods for those living in the country’s poorest and most marginal communes . In particular, it would enhance performance of GoV’s targeted programs with respect to local-level empowerment, transparency and accountability; poverty targeting; and monitoring and evaluation (M&E). Expected key performance indicators would include (to be further specified during preparation): -Empowerment of local communities and ethnic minorities, assessed against their demonstrated capacity in directly managing investments and use of citizen report cards; --Instrumental benefits of empowerment seen in higher quality and cost-effectiveness of basic infrastructure investments in participating, by comparision with those in non-program communes; Poverty targeting as shown by the percentages of poor people included and non-poor excluded, and percentage of program investements that reach or benefit the poorest quintile of the population; Improved process monitoring and impact evaluation mechanisms applied in pratice and used to inform ongoing implementation.